PENINGKATAN KEMAMPUAN SOSIAL EMOSIONAL MELALUI BERMAIN PERAN BERBASIS MARKET DAY USIA 4-5 TAHUN DI POS PAUD KEMUNING 18 TAHUN 2026 - Wati, Linda; M. Fadil Djamali; Muhammad Agus Sugiarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of social emotional abilities of children aged 4-5 years at POS PAUD Kemuning 18, which is caused by the teaching and learning methods used are still rudimentary in lecture techniques and the tools used are limited to books, so that the stimulation provided is not optimal. This study aims to support the social emotional development of children aged 4-5 years through the role play method based on market day as an active learning method. The approach used is the Classroom Action Research (CAR) model of Kemmis and Mc Taggart, which was carried out in two cycles with the steps of planning, implementation, observation, and reflection. The results of the study showed that in cycle 1, children's social emotional abilities had not developed optimally, with only 3 children achieving Still Developing (MB), and 4 students obtaining the classification of Developing According to Expectations (BSH) out of 7 children. After improvements were made to learning in cycle 2, there was an increase, where 2 children obtained the classification of Developing According to Expectations (BSH) and 4 students obtained Very Good Development (BSB) out of 7 children. With a success percentage of up to 85%. This improvement demonstrates that the use of market day-based role-playing as an engaging learning method can increase learning interest, activeness, and the ability of children who are not yet able to cooperate and develop self-confidence. Therefore, the learning activities implemented were successful in improving the social and emotional development of early childhood.